Addressing the Timber Trade Crisis Amidst the Pandemic: ASEAN Strategy Within the ASEAN Comprehensive Recovery Framework (ACRF) From a Regime Transformation Perspective - Sari, Octavia Novita; Hayatunufus; Heyna Jekaisa; Indra Wahyu Pratama; Muslihah Faradila (Journal of World Trade Studies, 2023)
This article aims to explore how the ASEAN Comprehensive Recovery Framework (ACRF) is employed by member countries as an exit strategy to address the COVID-19-induced crisis, particularly focusing on the timber trade. The creation of ACRF, specifically in tackling the timber sector crisis, becomes intriguing due to the distinct impact of the COVID-19 pandemic on timber trade between VPA and non-VPA countries. This study delves into elucidating how the ACRF functions as a solution to the timber trade crisis among ASEAN member states. Utilizing a qualitative explanatory research method, the analysis reveals that VPA countries leverage the ACRF as a collaborative framework to rejuvenate the timber industry, considering it an essential tool to enhance their dominance in the ASEAN timber sector. The ACRF, deployed to address the timber trade crisis amid the pandemic, represents a strategic shift in ASEAN's regime transformation. Specifically, ACRF Strategy 3, focusing on Maximizing Intra-ASEAN Market Potential and Wider Economic Integration, particularly point 3.d, eliminating Non-Tariff Barriers (NTBs) and reducing market-distorting policies is intricately linked to the ASEAN Trade in Goods Agreement (ATIGA).